2012
DOI: 10.1161/hypertensionaha.111.182923
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoexcitation by Brain Oxidative Stress Mediates Arterial Pressure Elevation in Salt-Induced Chronic Kidney Disease

Abstract: Abstract-Hypertension is very prevalent in chronic kidney disease and critical for its prognosis. Sympathoexcitation and oxidative stress have been demonstrated to be involved in chronic kidney disease. We have shown previously that sympathoexcitation by brain oxidative stress mediates arterial pressure elevation in the salt-sensitive hypertension model, Dahl salt-sensitive rats. Thus, we investigated whether sympathoexcitation by excessive brain oxidative stress could contribute to arterial pressure elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…Similarly, an overexpression of the brain RAS in DSS rats contributes to their hypertension, 48 whereas an inhibition of brain ROS and sympathoexcitation in salt-loaded uninephrectomized rats by tempol lessens hypertension. 49 However, the SNS, rather than hypertension, linked the brain and renal RAS because normalization of BP with hydralazine failed to prevent these responses to salt in 5/6Nx rats. Consistent with the hypothesis, salt-induced renal fibrosis and dysfunction were improved significantly in rats after central blockade of RAS or sympathetic outflow, in contrast with those treated with hydralazine.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an overexpression of the brain RAS in DSS rats contributes to their hypertension, 48 whereas an inhibition of brain ROS and sympathoexcitation in salt-loaded uninephrectomized rats by tempol lessens hypertension. 49 However, the SNS, rather than hypertension, linked the brain and renal RAS because normalization of BP with hydralazine failed to prevent these responses to salt in 5/6Nx rats. Consistent with the hypothesis, salt-induced renal fibrosis and dysfunction were improved significantly in rats after central blockade of RAS or sympathetic outflow, in contrast with those treated with hydralazine.…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitory action for salt on neuronal NOS expression in the posterior hypothalamic nuclei, the locus coeruleus, and the PVN was suggested by Campese et al [150] as a possible mechanism related to the high-salt-mediated action of the SNS. A role also was proposed for brain oxidative stress in driving sympathoexcitation in response to salt load in uninephrectomized rats [151].…”
Section: Saltmentioning
confidence: 99%
“…Activation of these PVN neurons can lead to sympathetic discharge (20,45). Multiple factors affect sympathetic outflow such as sodium, ANG II, glutamate, cytokines, oxidative stress, and nitric oxide (NO) (11,12,34,41,47). Previous studies have demonstrated that brain PRR activation can increase the production of inflammatory cytokines, oxidative stress, and ANG II (32,37,46).…”
mentioning
confidence: 99%